Effects of Pulmonary Rehabilitation on Body Mass Index In Patients With Copd (Journal of Dhaka National Medical College & Hospital, 2014)
Background: COPD is preventable, as well as treatable disease with some important extra pulmonary effects which may contribute to the severity of this disease. Pulmonary rehabilitation (PR) is known to be beneficial treatment for COPD patients.Objective: To evaluate the effects of pulmonary rehabilitation on anthropometry in male patients with moderate stable COPD.Methods: This prospective study was conducted in the Department of Physiology, BSMMU, Dhaka from 1st July 2010 to 30th June 2011 on 116 male stable moderate COPD patients aged 50 to 65 years. They were enrolled from the OPD of the Department of  Medicine of  BSMMU and NIDCH Dhaka. All the patients were grouped as control (56 patients without rehabilitation) and experimental (60 patients with rehabilitation). Pulmonary Rehabilitation (PR) program includes breathing exercises (pursed lip breathing and diaphragmatic breathing) and lower extremity endurance training (ground based walking); and was advised to the experimental patients to perform for 30 minutes duration per session at home twice daily, for consecutive 60 (Sixty) days along with the standard drug treatment of COPD. On the contrary, the control patients were advised to continue their standard drug treatment alone for consecutive 60 days. Anthropometry was assessed by measuring the BMI. Study variable was assessed on day 0 and day 60 for both the groups and the statistical analysis was done by independent sample ‘t’ test and paired Student’s ‘t’ test. In the interpretation of results, p≤0.05 was accepted, as level of significance.Results: BMI was significantly increased in comparison to the control patients after 60 days of follow up.Conclusion: The study reveals improvement of BMI with this sort of combination of PR program in stable COPD patients.J. Dhaka National Med. Coll. Hos. 2014; 20 (02) : 6-10